Dithieno[3,2-f:2′,3′-h]quinoxaline-Based Photovoltaic–Thermoelectric Dual-Functional Energy-Harvesting Wide-Bandgap Polymer and its Backbone Isomer - Yoon, Seong Jun; Choi, Kang Suh; Zhong, Lian; Jeong, Seonghun; Cho, Yongjoon; Jung, Sungwoo; Yoon, Sang Eun; Kim, Jong H.; Yang, Changduk (Small, 2023)
Both organic solar cells (OSCs) and organic thermoelectrics (OTEs) are promising energy-harvesting technologies for future renewable and sustainable energy sources. Among various material systems, organic conjugated polymers are an emerging material class for the active layers of both OSCs and OTEs. However, organic conjugated polymers showing both OSC and OTE properties are rarely reported because of the different requirements toward the OSCs and OTEs. In this study, the first simultaneous investigation of the OSC and OTE properties of a wide-bandgap polymer PBQx-TF and its backbone isomer iso-PBQx-TF are reported. All wide-bandgap polymers form face-on orientations in a thin-film state, but PBQx-TF has more of a crystalline character than iso-PBQx-TF, originating from the backbone isomeric structures of α,α ′/β,β ′-connection between two thiophene rings. Additionally, iso-PBQx-TF shows inactive OSC and poor OTE properties, probably because of the absorption mismatch and unfavorable molecular orientations. At the same time, PBQx-TF exhibits both decent OSC and OTE performances, indicating that it satisfies the requirements for both OSCs and OTEs. This study presents the OSC and OTE dual-functional energy-harvesting wide-bandgap polymer and the future research directions for hybrid energy-harvesting materials.
Keywords: Backbone isomer study; Band-gap polymers; Dual-functional energy harvesting; Organic thermoelectric; Organics; Quinoxalines; Thermoelectric; Thermoelectric properties; Wide-band-gap; Wide-bandgap polymer; backbone isomer study; dual-functional energy harvesting; organic solar cells; organic thermoelectric; wide-bandgap polymers